SKILLS ON THE DETECTION OF EARLY MOTHER FLOWER GROW WITH BABY - Sari, Dewi Ika; Palasari, Wina (Jurnal Penelitian STIKES Kediri, 2012)
Baby’s growth and development is a developmental foundation that will influence and determine growth and development further, so that it is needed skills and the roles of mother for their growth and development as a whole process. The objective is to identify deficiencies or excess of the baby’s development process as early as possible and may provide stimulation holistically to their physic, mental, and social. The design used in this research was correlation. The populations were mother and her baby in out-patient installation Kediri baptist hospital. the samples were 81 respondents using simple random sampling. the independent variable was skill of mother and the dependent variable was growth and development. The data was collected using questionnaire and measurement of weight and height, then analyzed using statistical test of Mann-Whitney with significant level of α ≤ 0,05. The result of this research showed that most of respondent had good skills in early detection and baby’s growth and development, they were 58 respondents (72%). The result statistical test of spearman’s rho was p = 0,003, it meant ha was accepted and ho was rejected. In conclusion of this research that there was Correlation between mother’s skills on early detection of growth and development and baby’s growth and development in out-patient installation Kediri Baptist Hospital.